Preparation method and application of SERS substrate based on CFRP / Ag composite material

Through the preparation method of SERS substrate based on CFRP/Ag composite materials, the problems of insufficient detection sensitivity and poor stability of low-concentration organic molecules in the prior art are solved, and high sensitivity detection and good stability of 10-12M concentration organic molecules are achieved.

CN119619104APending Publication Date: 2025-03-14JILIN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411772004.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing SERS substrates have insufficient sensitivity and poor stability in the detection of low concentration organic molecules.

Method used

Using the SERS substrate preparation method based on CFRP/Ag composite material, concentrated silver nanoparticles were prepared and spin-coated to the surface of the pretreated carbon fiber composite material, combining electromagnetic reinforcement and chemical reinforcement mechanisms.

Benefits of technology

High sensitivity detection of low-concentration organic molecules is achieved, the stability and uniformity of the SERS substrate are improved, and effective detection can be carried out at a concentration of 10-12M rhodamine 6G.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119619104A_ABST
    Figure CN119619104A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an SERS (Surface Enhanced Raman Scattering) substrate based on a CFRP / Ag composite material, and relates to the technical field of Raman detection.The preparation method comprises the steps that firstly, concentrated silver nanoparticles are prepared; then carrying out pretreatment on a carbon fiber composite material CFRP; finally, the pretreated CFRP is placed on a spin coater, the surface of the CFRP is spin-coated with concentrated silver nanoparticles for 2 min, then the CFRP is placed in a vacuum drying oven to be dried, and the SERS substrate based on the CFRP / Ag composite material is obtained. According to the preparation method and application of the SERS substrate based on the CFRP / Ag composite material, the SERS substrate is composed of the carbon fiber composite material and the silver nanoparticles, so that the excellent SERS enhancement effect of the silver nanoparticles and the advantages of low cost, good stability and good adsorption performance of CFRP are combined, and the SERS substrate shows good SERS performance in the aspects of sensitivity, stability and uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to Raman detection technology, and in particular to a SERS substrate preparation method and application based on CFRP / Ag composite materials. Background Art

[0002] Surface enhanced Raman substrate (SERS substrate) is a substrate material used to enhance Raman scattering signals and is an important component of surface enhanced Raman scattering (SERS) spectroscopy. In traditional Raman spectroscopy, samples usually need to have a high concentration or volume to obtain sufficient signal intensity, while the use of surface enhanced Raman substrates can significantly increase the signal intensity, allowing effective analysis even at low concentrations.

[0003] SERS is a surface sensitive technology. When molecules are adsorbed onto the surface of metal nanoparticles (such as gold, silver, copper, etc.) with special structures or properties, the Raman scattering signal will be significantly enhanced. SERS has the advantages of high sensitivity, fast detection speed, non-destructiveness and no interference from water molecules. Therefore, SERS plays an important role in scientific research such as single molecule detection, chemical reaction mechanism and cell behavior in vivo. At the same time, it is also increasingly widely used in real life such as food safety, environmental pollution and art authentication. To achieve high-sensitivity detection of SERS, the substrate structure is crucial.

[0004] However, the SERS substrates in the prior art often face the problems of insufficient sensitivity and poor stability, especially in the detection of low-concentration organic molecules. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a SERS substrate based on a CFRP / Ag composite material and its application, so as to solve the problems of insufficient sensitivity and poor stability in the prior art in the detection of low-concentration organic molecules.

[0006] In order to achieve the above object, the present invention provides the following technical solution: a method for preparing a SERS substrate based on a CFRP / Ag composite material, comprising:

[0007] S1. First, concentrated silver nanoparticles are prepared;

[0008] S2, then pre-treating the carbon fiber composite material CFRP to obtain the pre-treated CFRP;

[0009] S3. Finally, the pretreated CFRP was placed on a coater, and the concentrated silver nanoparticles were spin-coated onto the surface of the CFRP for 2 minutes. The CFRP was then placed in a vacuum drying oven for drying to obtain a SERS substrate based on the CFRP / Ag composite material.

[0010] Furthermore, the acceleration of the glue-spinning machine in S3 is 200 r·min -1 ·s -1 , the rotation speed of the glue spreader S3 is 3000r / min.

[0011] Furthermore, the temperature of the vacuum drying oven in S3 is 60°C.

[0012] Furthermore, the step S1 first prepares concentrated silver nanoparticles, comprising:

[0013] S11, dissolving silver nitrate in deionized water, heating to a slightly boiling state under magnetic stirring, adding sodium citrate solution, continuing to heat to boiling, heating and stirring for one hour, and cooling to room temperature to obtain silver nanoparticles;

[0014] S12. After centrifuging the silver nanoparticles, remove the supernatant and add deionized water to obtain concentrated silver nanoparticles.

[0015] Furthermore, the mass fraction of the sodium citrate solution in S11 is 1%.

[0016] Furthermore, the centrifugal speed in S12 is 6000×g and the centrifugal time is 10 min.

[0017] Further, in S2, the carbon fiber composite material CFRP is then pretreated, including:

[0018] S21, using carbon fiber composite material CFRP as the base support material, firstly grinding the surface of CFRP with sandpaper;

[0019] S22, ultrasonically cleaning the polished CFRP with acetone, ethanol and deionized water for 30 minutes respectively, then placing it in a sodium hydroxide solution, boiling it for 30 minutes, and then taking it out and cleaning it with deionized water;

[0020] S23, soaking the cleaned CFRP in a concentrated nitric acid solution for 2 hours, taking it out, washing it with deionized water, and drying it under a nitrogen gas flow to obtain a pretreated CFRP.

[0021] Furthermore, the concentration of the sodium hydroxide solution in S22 is 1 mol / L.

[0022] Furthermore, the mass fraction of the concentrated nitric acid solution in S23 is 65%.

[0023] Application of a SERS substrate based on a CFRP / Ag composite material prepared by the preparation method in organic molecule detection.

[0024] Compared with the prior art, the SERS substrate preparation method and application based on CFRP / Ag composite material provided by the present invention, the CFRP / Ag composite nanomaterial is composed of carbon fiber composite material and silver nanoparticles, thereby combining the excellent SERS enhancement effect of silver nanoparticles with the advantages of low cost, good stability and good adsorption performance of CFRP, making full use of electromagnetic enhancement and chemical enhancement mechanisms, and showing good SERS performance in terms of sensitivity, stability and uniformity;

[0025] CFRP / Ag composites have higher sensitivity as SERS substrates. The detection limit of Rhodamine 6G on the prepared SERS substrate based on CFRP / Ag composites reached 10 -12 M, thereby enabling detection of organic molecules at low concentrations; and the SERS substrate based on the CFRP / Ag composite material has good uniformity and stability, and can achieve repeatable signal detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.

[0027] Figure 1 The SEM image of the SERS substrate based on the CFRP / Ag composite material provided in the embodiment of the present invention;

[0028] Figure 2 XRD diagram of a SERS substrate based on a CFRP / Ag composite material provided in an embodiment of the present invention;

[0029] Figure 3 Common Raman spectra of CFRP and CFRP / Ag provided in the embodiments of the present invention;

[0030] Figure 4 The SERS spectra of the CFRP / Ag composite system SERS substrate provided in the embodiment of the present invention for detecting Rhodamine 6G molecules with different concentrations;

[0031] Figure 5 The embodiments of the present invention provide glass / Ag and silicon / Ag composite materials as SERS substrates to measure SERS spectra of Rhodamine 6G molecules with different concentrations;

[0032] Figure 6 A graph showing the uniformity detection results of a SERS substrate based on a CFRP / Ag composite material provided in an embodiment of the present invention;

[0033] Figure 7 A graph showing the enhancement effect of a newly prepared SERS substrate and a SERS substrate sealed and stored for 30 days provided in an embodiment of the present invention;

[0034] Figure 8 The overall flow chart of the preparation method provided by the embodiment of the present invention. DETAILED DESCRIPTION

[0035] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.

[0036] Embodiment 1:

[0037] See also Figure 8 , a method for preparing a SERS substrate based on a CFRP / Ag composite material, comprising:

[0038] S1. First, concentrated silver nanoparticles are prepared;

[0039] S11, dissolving silver nitrate in deionized water, heating to a slightly boiling state under magnetic stirring, adding sodium citrate solution, continuing to heat to boiling, heating and stirring for one hour, cooling to room temperature, and obtaining silver nanoparticles; the mass fraction of the sodium citrate solution is 1%;

[0040] S12. After the silver nanoparticles are centrifuged, the supernatant is removed and deionized water is added to obtain concentrated silver nanoparticles; the centrifugal speed is 6000×g and the centrifugal time is 10 min.

[0041] The specific implementation method is to weigh 40 mg of silver nitrate AgNO3 to ensure that its purity meets the experimental requirements; prepare 200 mL of deionized water to dissolve the silver nitrate; prepare 4 mL of a 1% sodium citrate (C6H3Na3O7) solution as a reducing agent.

[0042] Add the weighed silver nitrate to 200 mL of deionized water and stir thoroughly with a magnetic stirrer to ensure that the silver nitrate is completely dissolved. Heat the solution to a slight boil under magnetic stirring. At this point, pay attention to controlling the heating speed to avoid missing the best time to add the reducing agent.

[0043] When the solution reaches a slightly boiling state, slowly add 4 mL of 1% sodium citrate solution. Sodium citrate acts as a reducing agent to reduce the silver ions Ag in silver nitrate. + , thereby generating silver nanoparticles; continue to heat the solution to boiling and maintain magnetic stirring. The heating and stirring process should last for one hour to ensure that the silver nanoparticles are fully generated and stabilized.

[0044] After heating and stirring for one hour, the solution was cooled naturally to room temperature. After cooling, 50 mL of the silver nanoparticle solution was centrifuged at 6000×g for 10 minutes.

[0045] After centrifugation, the supernatant was removed, and the lower precipitate was silver nanoparticles; 5 mL of deionized water was added to the precipitate, and ultrasonic treatment was performed for 5 minutes to redisperse the silver nanoparticles in the deionized water to obtain a concentrated silver nanoparticle sol.

[0046] S2, then pre-treating the carbon fiber composite material CFRP to obtain the pre-treated CFRP;

[0047] S21, using carbon fiber composite material CFRP as the base support material, firstly grinding the surface of CFRP with sandpaper;

[0048] S22, the polished CFRP was ultrasonically cleaned with acetone, ethanol and deionized water for 30 minutes respectively, then placed in a sodium hydroxide solution, boiled for 30 minutes, and then taken out and cleaned with deionized water; the concentration of the sodium hydroxide solution was 1 mol / L;

[0049] S23, soaking the cleaned CFRP in a concentrated nitric acid solution for 2 hours, taking it out, washing it with deionized water, and drying it under a nitrogen flow to obtain a pretreated CFRP; the mass fraction of the concentrated nitric acid solution is 65%.

[0050] The specific implementation method is to select a carbon fiber composite material (CFRP) with a size of 1×1 cm as the base support material. The material has good chemical stability and mechanical strength as well as a large specific surface area, and has potential application value in the adsorption and immobilization of silver nanoparticles.

[0051] Use sandpaper of appropriate grain size to carefully polish the CFRP surface to remove the original smooth layer on the surface and increase its roughness. During the polishing process, attention should be paid to uniform strength to avoid excessive wear and damage to the substrate structure. The purpose of this step is to increase the specific surface area of ​​the CFRP surface, which is conducive to the subsequent adsorption and fixation of silver nanoparticles.

[0052] The polished CFRP was placed in an acetone solution and cleaned using an ultrasonic cleaner for 30 minutes. Acetone, as an organic solvent, can effectively remove organic pollutants such as grease and oil on the surface of the CFRP.

[0053] After the CFRP is taken out of the acetone solution, it is immediately placed in an ethanol solution and cleaned again using an ultrasonic cleaner for the same 30 minutes; ethanol can further remove residues on the surface of the CFRP.

[0054] After the CFRP was removed from the ethanol solution, it was thoroughly rinsed with deionized water to remove all residual solvent and impurities.

[0055] Place the cleaned CFRP in a 1 mol / L sodium hydroxide solution, heat to boiling, and keep boiling for 30 minutes. The sodium hydroxide solution can remove organic and inorganic attachments on the surface of the CFRP and further clean its surface. During the boiling process, care should be taken to control the heating speed and temperature to avoid damage to the CFRP due to high temperature.

[0056] After removing the CFRP from the sodium hydroxide solution, clean it with deionized water and then soak it in a 65% concentrated nitric acid solution for 2 hours. Concentrated nitric acid can further remove the residue on the surface of the CFRP and chemically modify its surface to a certain extent, which is conducive to the adsorption of silver nanoparticles. During the soaking process, pay attention to observe the changes on the CFRP surface to ensure that the treatment time is appropriate.

[0057] After the CFRP is removed from the concentrated nitric acid solution, it is thoroughly washed with deionized water to remove the residual acid and impurities. The CFRP is then blown dry under a nitrogen flow to ensure that the surface is dry and free of moisture.

[0058] S3. Finally, the pretreated CFRP was placed on a coater, and the concentrated silver nanoparticles were spin-coated onto the surface of the CFRP for 2 minutes. The CFRP was then placed in a vacuum drying oven for drying to obtain a SERS substrate based on the CFRP / Ag composite material.

[0059] The pre-treated carbon fiber composite material (CFRP) is fixed on the rotating platform of the sizing machine to ensure that the CFRP surface is flat and the center is aligned with the rotation axis. Then, 20 microliters (20μL) of concentrated silver nanoparticle sol is accurately drawn with a micropipette and evenly dropped on the center area of ​​CFRP.

[0060] Start the glue machine and set the acceleration to 200r·min -1 ·s -1 , that is, the acceleration increases by 200 rpm per second to achieve a gradual acceleration effect and avoid splashing of the solution caused by instantaneous high-speed rotation. When the preset acceleration is reached, the coating machine will rotate at a constant speed of 3000r / min, and the spin coating time is 2 minutes.

[0061] After the spin coating is completed, the CFRP is removed from the coating machine and immediately placed in a vacuum drying oven at 60 degrees Celsius. The vacuum drying oven can provide a low-oxygen, low-humidity environment, which helps to accelerate the volatilization of the solvent and the curing of the silver nanoparticle film. Dry at 60 degrees Celsius for 5 hours until the silver nanoparticle film on the surface of the CFRP is completely dry and no solvent remains.

[0062] After the above steps, the surface of CFRP will be covered with a thin film composed of concentrated silver nanoparticles, thereby obtaining a SERS (surface enhanced Raman scattering) substrate based on CFRP / Ag composite material.

[0063] Embodiment 2:

[0064] See also Figure 1-Figure 3 This embodiment provides a technical solution based on the first embodiment: performing relevant characterization tests on a SERS substrate based on a CFRP / Ag composite material.

[0065] 1. Microscopic morphology observation by scanning electron microscope (SEM) test:

[0066] Figure 1 A is the SEM image of carbon fiber, from which it can be seen that the diameter of the carbon fiber is about 7μm, the surface is uneven, and there are many longitudinal grooves; the presence of grooves can increase the contact area between the carbon fiber and the silver nanoparticles, which is conducive to the generation of "hot spots".

[0067] Figure 1 B is a SEM image of silver nanoparticles loaded on the surface of carbon fiber. Most of the silver nanoparticles have a diameter of 50 nm and are distributed on the surface of carbon fiber in an aggregated state.

[0068] 2. Material structure analysis through X-ray diffraction (XRD) test:

[0069] See also Figure 2 Obvious characteristic peaks were detected at 25.5°, 38.1°, 44.1°, 64.4° and 77.3°. The characteristic peaks were compared and analyzed using JADE software. These peaks were attributed to the (002) crystal plane of carbon and the (111), (200), (220) and (311) crystal planes of silver, respectively, indicating that the CFRP / Ag sample was successfully prepared.

[0070] 3. Raman spectroscopy test of CFRP and CFRP / Ag:

[0071] Raman spectroscopy is a non-destructive analytical technique based on the Raman scattering effect, which is used to study molecular vibrations and structures. When a laser irradiates a sample, most of the light is scattered at the same frequency, which is called Rayleigh scattering, while a small part of the light changes frequency due to interaction with molecules, which is called Raman scattering. This frequency change corresponds to the transition of molecular vibration energy levels, forming characteristic Raman peaks, and molecular structure information can be obtained by analyzing these peaks.

[0072] See also Figure 3 , the common Raman spectra of CFRP and CFRP / Ag, the main peak in the figure is located at 1350cm -1 and 1577cm-1 At , they correspond to the D peak and G peak of carbon fiber, respectively, which is consistent with the known data.

[0073] Embodiment three:

[0074] See also Figure 4 This embodiment provides a technical solution based on the first embodiment: performing detection limit-related tests on a SERS substrate based on a CFRP / Ag composite material.

[0075] Rhodamine 6G molecule is a commonly used probe molecule for detecting the performance of SERS substrates, and its SERS signal is very sensitive to the substrate material.

[0076] By observing the SERS signals of Rhodamine 6G on different substrates, the SERS enhancement effect, uniformity, stability and other properties of the substrate can be intuitively judged.

[0077] Prepare the concentration of 10 -6 M, 10 -7 M, 10 -8 M, 10 -9 M, 10 -10 M, 10 -11 M, 10 -12 M of Rhodamine 6G solution, take 20 μL of each of the above Rhodamine 6G solutions of different concentrations and drop them on the SERS substrate respectively, leave them at room temperature, wait for the solvent to evaporate completely, until they are dry, and perform Raman spectroscopy detection with an excitation wavelength of 532 nm, a 50x objective lens, an exposure time of 1 s, and 1 exposure time.

[0078] See also Figure 4 , SERS spectrum of CFRP / Ag composite system SERS substrate for rhodamine 6G molecule detection. From the figure, it can be clearly observed that the -1 (CCC in-plane vibration), 772cm -1 (CH out-of-plane vibration), 1181cm -1 (CH out-of-plane vibration), 1358cm -1 (CH in-plane bending vibration), 1503cm -1 (CC stretching vibration) and 1642cm -1 The Raman characteristic peak of (C-C stretching vibration) is consistent with the known data.

[0079] In general, Rhodamine 6G is present at a concentration of 10 -6 When the concentration was 10 M, its Raman scattering signal could not be observed. However, when CFRP / Ag was used as the SERS substrate, the signal of the rhodamine 6G molecule could be clearly observed. -6 M down to 10 -12M, the SERS spectrum intensity gradually weakened; when the concentration dropped to 10 -12 M, the characteristic peak of rhodamine 6G can still be observed. This shows that the detection limit of the prepared CFRP / Ag composite system SERS substrate for rhodamine 6G has reached 10 -12 M, so samples with lower concentrations can be analyzed.

[0080] Embodiment 4:

[0081] See also Figure 5 This embodiment provides a technical solution based on the second embodiment: verifying the Raman enhancement effect of CFRP as a SERS substrate support material, and conducting relevant comparative experiments.

[0082] Under the same experimental conditions, a silicon wafer and a glass wafer were used as substrates, respectively, and concentrated silver nanoparticles were spin-coated on the surfaces thereof. The specific experimental steps were the same as step S3 in Example 1.

[0083] See also Figure 5 a, Using glass / Ag composite material as SERS substrate, the SERS spectra of Rhodamine 6G molecules with different concentrations were measured. The spectral intensity decreased with the decrease of concentration, and the detection limit was 10 -7 M. See Figure 5 b. Using silicon / Ag composite material as SERS substrate, under the same detection conditions, the detection limit of rhodamine 6G molecules is 10 -8 M. By Figure 4 By comparison, it can be seen that CFRP / Ag composite material as a SERS substrate has higher sensitivity and can realize the detection of organic molecules at low concentrations.

[0084] Embodiment five:

[0085] See also Figure 6-Figure 7 This embodiment provides a technical solution based on the first embodiment: performing uniformity-related tests on a SERS substrate based on a CFRP / Ag composite material.

[0086] Uniformity is also an important indicator for evaluating the performance of SERS active substrates. Although the sensitivity of surface enhanced Raman substrates is very high, if the substrate is not uniform enough, the Raman signals detected at different parts of the substrate will be quite different, and such SERS substrates are not practical.

[0087] Different positions were randomly selected on the substrate to detect the Raman signal of the probe molecule. The concentration of rhodamine 6G was 10 -6 M.

[0088] See also Figure 6a, The SERS signals detected at 8 randomly selected points have basically the same intensity, with no obvious difference; see Figure 6 b- Figure 6 d, respectively, for the same sample at 611 cm -1 、772cm -1 and 1642cm -1 The relative standard deviations (RSD) at the positions are calculated to be 4.3%, 4.2% and 5.6% respectively. The above analysis shows that the CFRP / Ag composite SERS substrate prepared by the present invention has good uniformity and can achieve repeatable signal detection.

[0089] The stability of the SERS substrate based on the CFRP / Ag composite material was further tested, and the enhancement effect of the newly prepared SERS substrate was compared with that of the SERS substrate sealed and stored for 30 days. Figure 7 See Figure 7 After 30 days of storage, its SERS activity only decreased by 3.1%, indicating that the SERS substrate based on CFRP / Ag composite material has good stability.

[0090] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a SERS substrate based on a CFRP / Ag composite material, characterized in that: include: S1. First, concentrated silver nanoparticles are prepared; S2, then pre-treating the carbon fiber composite material CFRP to obtain the pre-treated CFRP; S3. Finally, the pretreated CFRP was placed on a coater, and the concentrated silver nanoparticles were spin-coated onto the surface of the CFRP for 2 minutes. The CFRP was then placed in a vacuum drying oven for drying to obtain a SERS substrate based on the CFRP / Ag composite material.

2. The method for preparing a SERS substrate based on a CFRP / Ag composite material according to claim 1, characterized in that: The acceleration of the glue machine in S3 is 200r·min -1 ·s -1 , the rotation speed of the glue spreader S3 is 3000r / min.

3. The method for preparing a SERS substrate based on a CFRP / Ag composite material according to claim 1, characterized in that: The temperature of the vacuum drying oven in S3 is 60°C.

4. The method for preparing a SERS substrate based on a CFRP / Ag composite material according to claim 1, characterized in that: S1 first prepares concentrated silver nanoparticles, including: S11, dissolving silver nitrate in deionized water, heating to a slightly boiling state under magnetic stirring, adding sodium citrate solution, continuing to heat to boiling, heating and stirring for one hour, and cooling to room temperature to obtain silver nanoparticles; S12. After centrifuging the silver nanoparticles, remove the supernatant and add deionized water to obtain concentrated silver nanoparticles.

5. The method for preparing a SERS substrate based on a CFRP / Ag composite material according to claim 4, characterized in that: The mass fraction of the sodium citrate solution in S11 is 1%.

6. The method for preparing a SERS substrate based on a CFRP / Ag composite material according to claim 4, characterized in that: The centrifugal speed in S12 is 6000×g, and the centrifugal time is 10 min.

7. The method for preparing a SERS substrate based on a CFRP / Ag composite material according to claim 1, characterized in that: S2 then pre-treats the carbon fiber composite material CFRP, including: S21, using carbon fiber composite material CFRP as the base support material, firstly grinding the surface of CFRP with sandpaper; S22, ultrasonically cleaning the polished CFRP with acetone, ethanol and deionized water for 30 minutes respectively, then placing it in a sodium hydroxide solution, boiling it for 30 minutes, and then taking it out and cleaning it with deionized water; S23, soaking the cleaned CFRP in a concentrated nitric acid solution for 2 hours, taking it out, washing it with deionized water, and drying it under a nitrogen gas flow to obtain a pretreated CFRP.

8. The method for preparing a SERS substrate based on a CFRP / Ag composite material according to claim 7, characterized in that: The sodium hydroxide solution concentration described in S22 is 1 mol / L.

9. The method for preparing a SERS substrate based on a CFRP / Ag composite material according to claim 7, characterized in that: The mass fraction of the concentrated nitric acid solution in S23 is 65%.

10. Application of a SERS substrate based on a CFRP / Ag composite material prepared by the preparation method according to any one of claims 1 to 9 in organic molecule detection.